Creative Approaches in Art Education to Enhance Students' Creativity - Wiflihani, Wiflihani; Suroso, Panji; Razak, Amir (Jurnal Pendidikan dan Penciptaan Seni, 2025)
This study explores the significant role of creative approaches in art education in fostering students' creativity and critical thinking. Art education encourages active engagement in the creative process by emphasizing exploration, improvisation, and the integration of innovative media. The findings indicate that providing space for experimentation enhances students' technical skills and strengthens their problem-solving and collaboration abilities. Furthermore, integrating technology into art education broadens students' artistic horizons through digital art forms, design software, and multimedia tools, making learning more dynamic and relevant. This study underscores the importance of creative pedagogy in preparing students for real-world challenges, equipping them with adaptability and innovation skills essential in the evolving modern landscape. The implications of these findings highlight the necessity of adopting creative strategies in art education to cultivate a more interactive, meaningful, and future-oriented learning experience.